THE REALIZATION OF COHESION IN THE SUDENTS' ARGUMENTATIVE WRITING PERFORMANCE - Saudin, H. (2013)
This research attempts to investigate the realization of cohesion in Argumentative texts written by nine second year college students in a test. They were selected purposively to represent their class and categorized into high, middle and low achievers. The investigation was conducted by applying a theoretical framework called the Patterns of Cohesion (Paltridge, 2006; Halliday and Matthiessen, 2004; Eggins, 2004; Salkie, 1995; and Gerot, 1994), which are subsumed under the Systemic Functional Linguistics (SFL). The patterns adopted in this research are extended and consist of seven cohesive devices, reference, conjunction, lexical cohesion, ellipsis, substitution, tense consistency and grammatical parallelism. As such, cohesion was investigated in its more complete construct. Further, the realization of cohesion was analyzed in two respects, the deployment and the erroneous employment of the cohesive devices. The results of the analysis, conducted qualitatively and quantitatively, showed that the deployment was different across the three proficiency levels. The higher the students' proficiency was, the denser the cohesive ties they deployed were. The analysis of the erroneous employment of the devices across the students' texts confirmed the differences. The lower their level was, the more errors they made in using the cohesive ties. Their oral performances during the interview also strengthened these differences in realizing the cohesive devices. Furthermore, the results revealed that lexical cohesion, regardless of the proficiency levels, was a predominant cohesive tie as some other studies had shown (Witte and Faigley, 1981; Hoey, 1991; Karasi, 1994; Meisuo, 2000; and Liu and Braine, 2005). Lexical cohesion made the most contribution to the texts' cohesive density, followed consecutively by reference, tense consistency, conjunction, grammatical parallelism, ellipsis and substitution. It was also revealed that heavy reliance on repetition might indicate low writing quality and the predominance of collocation high writing quality. The research suggests that lexical cohesion, not reference, be mentioned first in the theory of Patterns of Cohesion. It is also suggested that tense consistency and grammatical parallelism need to be included as cohesive devices. The former's contribution to the textual cohesion exceeded that of conjunction and the latter's surpassed that of ellipsis and substitution. In conclusion, it is proven that the effects of the cohesive devices on writing quality are positive. Therefore, writing teachers are suggested to prioritize exercises related to cohesion and integrate them into the teaching of writing to make the students have better writing performances.